Analysis of Labor Absorption in Art Shop Businesses in the Tourism Area of Kuta Village, Pujut District, Central Lombok Regency - Ningsih, Serli Martia; Fuadi, Helmy; Arini, Gusti Ayu (The Eastasouth Management and Business, 2024)
This research aims to analyze the influence of wages, turnover and length of business on labor absorption in art shop businesses in the Kuta Village tourism area, Pujut District, Central Lombok Regency. This study employs quantitative methodologies. This research utilizes primary data collected through the census method. The population in the study were 34 art shop businesses in the Kuta Village tourism area. This research employs a multiple linear regression analytical approach. The data analysis conducted using IBM SPSS 29 indicates that the pay variable exerts a negative and significant effect on labor absorption, whereas the turnover variable demonstrates a positive and substantial influence on labor absorption. Simultaneously, the length of the business variable exerts a favorable albeit insignificant influence on labor absorption within the art store sector. The research findings indicate that wages, turnover, and business longevity positively and significantly influence labor absorption in art shop enterprises.